KEBIJAKAN APLIKATIF PENJATUHAN PIDANA DENDA PASCA KELUARNYA PERMA NO. 2 TAHUN - Muhammad Iftar Aryaputra; Ani Triwati; Subaidah Ratna Juita (Universitas Semarang, 2017)
There are some problems with a formulation of fine in the Penal Code. These problems can be identified as follows, first, the number of fine in the Penal Code do not conform with the current state of the economy; second, the last change of nominal fine in the Penal Code is 1960 through Law (Prp) No. 18 of 1960; Third, the fine in the Penal Code already outdated when compared with the penalty of a fine in the special penal laws. The Supreme Court (MA) as the highest authority of the judiciary in Indonesia, issued Regulation No. 2 Year 2012. Issues examined in this study: (1) How to legislative policy (formulation) the reduction of crime by criminal penalties? How applicable are policies tackling crime in the Criminal Code with a penalty before and after the release of Perma No. 2 of 2012? The method used in this research is normative. In addition to using a normative approach, the research was supported by the approach of legislation and case approach. Secondary data as the primary data in this study primarily focused on legislation and court decisions, which were analyzed qualitatively.